To treasure an heiress - White, Roseanna M. (White, Roseanna M. Secrets of the isles, 2022)
"When Beth Tremayne stumbles across an old map, she pursues the excitement she's always craved. But her only way to piece together the clues is through Lord Sheridan-a man she insists stole a prized possession. As they follow the clues, they uncover a story of a piratical adventure, but the true treasure is the one they discover in one another"--